CONTRACEPTION CHOICE WHICH LEAD EXTREMELY CLOSE INTERPREGNANCY DISTANCE - Riska Faraswati; Mega Silvian Natalia (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2024)
Preventing unwanted or unplanned pregnancies is part of the national health programme. There are various negative impacts on pregnancies that occur between 3-12 months after delivery such as the risk of premature birth, psychological disorders, abortion, etc. Prevention programmes aim to reduces the number of unintended pregnancies. The aim of this study was to estimate the number of women who used contraception within 18 months after childbirth and the association between contraceptive methods used and risk of pregnancy within 18 months. A cross-sectional research method was chosen as research approach in mothers who gave birth to their first child in 2021 to 2022 conducted in Paiton Probolinggo district, data were collected from childbirth cohort records, contraceptive methods, information regarding re-pregnancy ≤ 18 months after previous delivery. The Fisher Exact Test statistical test results obtained a p value of 0.000 <0.05, 99% CI which shows that the choice of contraceptive method and the time of use have an impact on the interval of re-pregnancy.